2022
DOI: 10.3390/jcm11061494
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Carboxypeptidase U (CPU, TAFIa, CPB2) System in Patients with SARS-CoV-2 Infection Could Contribute to COVID-19 Hypofibrinolytic State and Disease Severity Prognosis

Abstract: Coronavirus disease 2019 (COVID-19) is a viral lower respiratory tract infection caused by the highly transmissible and pathogenic SARS-CoV-2 (severe acute respiratory-syndrome coronavirus-2). Besides respiratory failure, systemic thromboembolic complications are frequent in COVID-19 patients and suggested to be the result of a dysregulation of the hemostatic balance. Although several markers of coagulation and fibrinolysis have been studied extensively, little is known about the effect of SARS-CoV-2 infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
1
1
Order By: Relevance
“…Fibrinolysis is also modulated by TAFI, a carboxypeptidase that cleaves terminal lysine in fibrin, preventing t-PA-mediated plasminogen activation. We did not detect consumption of TAFI/TAFIa, in contrast to variable or increased levels reported in critically ill/ICU patients [14,17,20,52], suggesting that TAFIa also functions as a negative modulator of fibrinolysis in advanced conditions.…”
Section: Post-mortem Studiescontrasting
confidence: 92%
“…Fibrinolysis is also modulated by TAFI, a carboxypeptidase that cleaves terminal lysine in fibrin, preventing t-PA-mediated plasminogen activation. We did not detect consumption of TAFI/TAFIa, in contrast to variable or increased levels reported in critically ill/ICU patients [14,17,20,52], suggesting that TAFIa also functions as a negative modulator of fibrinolysis in advanced conditions.…”
Section: Post-mortem Studiescontrasting
confidence: 92%
“… 21 Levels of PAI‐1 are low in the circulation, but it is released from the endothelium, circulating platelets and adipocytes following stimulation. 22 Studies have indicated that the balance of fibrinolytic activators and inhibitors are altered in COVID‐19, however there is inadequate consensus on the drivers of the hypofibrinolytic state, with the suggestion that elevated fibrinogen, 23 , 24 TAFI, 24 , 25 tPA 26 , 27 and PAI‐1 24 , 28 , 29 or decreased plasminogen 28 , 30 are responsible.…”
Section: Introductionmentioning
confidence: 99%